SISTEM INFORMASI PELAYANAN SURAT KETERANGAN BERBASIS WEB PADA KANTOR KELURAHAN MATEKKO - Ispadilla Utami, Umrah; Candra, Adi; Nurul Faizah, Andi (CV. LAJAGOE PUSTAKA, 2024)
This study aims to: (1) Design an information system for Web-based certificate services at the Matekko Village Office. (2) Implementing a Web-based certificate service information system at the Matekko Village Office.This study uses the Waterfall research method, which is an information system development model that is carried out in a planned and sequential manner. The stages used in the Waterfal method include: (1) Requirements Definition/Requirements Analysis, (2) System and Software Design, (3) Implementation and Unit Testing, (4) Integration and Testing, (5) Operation and Maintenance.The results of research on information systems for Web-based certificate services at the Matekko Village Office, namely (1) this certificate service information system has been designed using sublime software as a text editor, MySQL Xampp 7 database management system (DBMS) and using the PHP programming language. (2) The Web-based certificate service information system at the Matekko Village Office that has been created is used for the management of certificates from the Village to make it easier. The test results show that this system is running well where the output is in accordance with what the user wants and can meet user needs in terms of managing a certificate from the village. This Web-based certificate service information system can be used by residents of the Matekko Village in managing certificates from the Village, it can also be used by village staff who act as system admins in terms of managing requests from residents for certificates from the village.